2023
DOI: 10.12659/msm.940128
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Gender, Frailty, and Body Mass Index on Serum IL-17A Levels in Mature Type 2 Diabetic Patients

Zvonimir Bosnić,
František Babič,
Thomas Wittlinger
et al.

Abstract: Background The cytokine IL-17A is emerging as a marker of chronic inflammation in cardio-metabolic conditions. This study aimed to identify relevant factors that in older primary care patients with type 2 diabetes (T2D) could influence serum IL-17A concentrations. The results have a potential to improve risk stratification and therapy options for these patients. Material/Methods The study was conducted during a period of 4 months, in 2020, in the south-eastern region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…One of the possible reasons for such discrepancies includes the wide range of age of studied diabetic patients that could have influenced the characteristics of clusters, in addition to differences in medications use. Furthermore, there are complex relationships between age, gender, postmenopausal status, T2DM duration, body shape, BMI categories, HbA1c, and inflammatory marker values as observed in previous studies 29 , 30 .…”
Section: Discussionmentioning
confidence: 72%
“…One of the possible reasons for such discrepancies includes the wide range of age of studied diabetic patients that could have influenced the characteristics of clusters, in addition to differences in medications use. Furthermore, there are complex relationships between age, gender, postmenopausal status, T2DM duration, body shape, BMI categories, HbA1c, and inflammatory marker values as observed in previous studies 29 , 30 .…”
Section: Discussionmentioning
confidence: 72%
“…This is especially true for elderly patients with T2D, where many factors interact in predicting the measurable outcomes, of which some may have alleviating effects and some may have worsening effects. In our recently published article, we demonstrated that the level of inflammation may vary among T2D patients, which is determined at least by variables such as age, sex, BMI and the level of frailty [ 33 ]. Any level of frailty, including mild, moderate and severe, was shown to increase the risk for all-cause and CV-related mortality in patients with CKD, but with different magnitudes of influence [ 85 ].…”
Section: T2d Patient Complexity and Endeavor Towards Precision Medicinementioning
confidence: 99%
“…Studies that assess the feasibility of using clustering techniques from data science application areas are underway, wanting to identify subcategories of patients with T2D that can be discriminated against in terms of CV and other poor outcomes and responses to treatment. Our research group has contributed to these efforts [ 32 , 33 , 89 ]. Regarding treatment, precision medicine looks at variations in drug effectiveness in specific patient subgroups and seeks markers (especially genetic markers) that can predict adverse drug events [ 87 ].…”
Section: T2d Patient Complexity and Endeavor Towards Precision Medicinementioning
confidence: 99%
See 2 more Smart Citations